Large negative thermal expansion in (Ga0.7Cu0.3)1-xMnxNMn3 (x ≤ 0.4), compensating for the thermal expansion of cryogenic materials. (February 2017) - Guo, X.G.; Tong, P.; Lin, J.C.; Yang, C.; Zhang, K.; Wang, M.; Wu, Y.; Lin, S.; Song, W.H.; Sun, Y.P.
Abstract: As the Mn doping level ( x ) increases in cubic (Ga0.7 Cu0.3 )1- x Mn x NMn3 ( x  ≤ 0.4) compounds, the temperature window of negative thermal expansion (NTE) is shifted to lower temperatures and broadened due to the strengthening of ferromagnetism. Large coefficient of linear thermal expansion ( α  ~ − 22.8 ppm/K) is observed for x  = 0.25 and 0.3 at cryogenic temperatures (< 120 K). By adding the x  = 0.3 powders, the thermal expansion of epoxy resin is effectively reduced. Nearly zero thermal expansion ( α ~  1 ppm/K) and remarkably improved thermal conductivity are achieved at cryogenic temperatures in the composite with 50 vol.% addition of the NTE filler. Graphical abstract: